2004
DOI: 10.1080/00071660410001668897
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phytase and xylanase, individually or in combination, on performance, apparent metabolisable energy, digestive tract measurements and gut morphology in broilers fed wheat-based diets containing adequate level of phosphorus

Abstract: 1. The aim of the present study was to examine the influence of microbial phytase and xylanase, individually or in combination, on performance, apparent metabolisable energy, digesta viscosity, digestive tract measurements and gut morphology in broilers fed on wheat-soy diets containing adequate phosphorus (P). The wheat-soy basal diet was formulated to contain 4.5 g/kg non-phytate P and the experimental diets were formulated by supplementing the basal diet with xylanase (1000 xylanase units/kg diet), phytase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
76
3
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 17 publications
19
76
3
7
Order By: Relevance
“…On that account, the enzyme addition is likely to have minimized such a response in organs of the digestive tract due to less need for enzyme secretion, thus, reducing the size of the gizzard and small intestine (Wang et al 2005). Similar results were found by Wu et al (2004) and Zhu et al (2014) in diets supplemented with exogenous enzymes. Furthermore, a decrease in the relative small intestine weight is indicative of less cell proliferation and, consequently, less of a maintenance requirement for this organ (Adeola and Cowieson 2011).…”
supporting
confidence: 76%
“…On that account, the enzyme addition is likely to have minimized such a response in organs of the digestive tract due to less need for enzyme secretion, thus, reducing the size of the gizzard and small intestine (Wang et al 2005). Similar results were found by Wu et al (2004) and Zhu et al (2014) in diets supplemented with exogenous enzymes. Furthermore, a decrease in the relative small intestine weight is indicative of less cell proliferation and, consequently, less of a maintenance requirement for this organ (Adeola and Cowieson 2011).…”
supporting
confidence: 76%
“…In the present study, relative abdominal fat weight was reduced with ground wheat feeding compared to whole wheat. In contrast, Wu et al (2004) found no effect of whole wheat inclusion on abdominal fat weights. Other researchers have reported higher relative abdominal fat weight when whole wheat was included (Jones and Taylor, 2001;Nahas and Lefrancois, 2001).…”
Section: Resultsmentioning
confidence: 67%
“…A decrease in the length of the intestine following supplementations is presumably related to more efficient and rapid digestion of nutrients (Marquardt, 1997). Accordingly, Wu et al (2004) reported that the addition of xylanase to ground wheat-based diets reduced the relative weight and length of the small intestine by 15.5% and 16.5%, respectively. In contrast, several authors (Brenes et al, 1993;Taylor and Jones, 2001) have previously indicated that xylanase supplementation did not significantly influence the relative weight and length of the intestine tract in chickens.…”
Section: Discussionmentioning
confidence: 99%